Reinforcing Steel Members and the Effects of Welding - Tide, Raymond H.R. (Engineering Journal, 1990)
Reinforcing structural steel compression members to increase the cross-sectional area or decrease slenderness by attaching additional bars, plates, angles and channels is an economical method of increasing load-carrying capacity. Supplemental reinforcement has been installed under various loading conditions. In most cases the attachment is achieved by welding, although bolting may be chosen for some particular technical or administrative reason. The author has been involved in both methods, and usually experience and the specific conditions dictate which attachment method is more appropriate. This paper presents a review of several proposed reinforcement methods and discusses factors that must be considered for each. The focus of this paper is welded reinforcement methods, although an appropriate reference to a bolted study is made. Whenever the existing steel members are in good condition and their composition is known, the welding requirements are straightforward. However, for older unknown or corroded steel, other factors are involved, such as weldability, contaminants and deep pitting. These issues were addressed by Tide and Ricker in earlier papers and are not repeated herein.